Circling back : chronicle of a Texas river valley - Truett, Joe C. (Joe Clyde), 1941- (American land and life series., 1996)
""There was so much space." These words epitomize ecologist Joe Truett's boyhood memories of the Angelina River valley in East Texas. Years and miles later, back home for the funeral of his grandfather, Truett began a long meditation on the world Corbett Graham had known and he himself had glimpsed, a now-vanished world where wild hogs and countless other animals rustled through the leaves, cows ate pinewoods grass instead of corn, oaks and hickories and longleaf pines were untouched by the corporate ax, and the river flowed freely. Truett's meditation resulted in this clear-sighted portrait of a place over time, its layers revealed by his love and care and curiosity." "Truett celebrates his family's heritage and the unspoiled natural world of the Piney Woods without nostalgia. He recreates an older, simpler, more worthy age, but he knows that we have lost touch with it because we wanted to: he laments the loss but understands it. What makes his prose so moving and so redeeming is this precise combination of honesty and sorrow, overlaid by a quiet passion for both the natural and the human worlds."--Jacket.